A Study on the Impact of Demographic Factors on Group Performance of Neighbourhood Groups (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper analyses the impact of demographic factors on the Neighbourhood Group (NHG)performance of Kudumbashree in Trivandrum, Kerala. The results showed that there is significant difference between that performances of the groups as the demographic factors differ. Analysis were done on the survey data collected from NHG.The paper also throws light on the aspects of homogeneity parameters which might have to be relooked while constituting the groups. Key factors like education and age are some very important aspects which can be used effectively to constitute the group.The authorities also can look at focal points which if intervened can considerably improve the performance. The purpose of joining the group also can be looked upon while considering the homogeneity. Paper focuses on demographics as the homogeneity is often overlooked and taken for granted in group formation which needs to be inquired.
Keywords: NHG; Performance; Demographic; Homogeneity; Improve; Formation